Production of habanero pepper (Capsicum chinense Jacq.) in vermicompost with organic fertilization - Javier-López, Leonel; Palacios-Torres, Rogelio Enrique; Ramírez-Seañez, Ana Rosa; Hernández-Hernández, Hipólito; Antonio-Luis, María del Carmen; Yam-Tzec, José Antonio; Chaires-Grijalva, Martha Patricia (Ecosistemas y Recursos Agropecuarios, 2022)
The indiscriminate use of chemical fertilization in agricultural production has caused serious damage to the environment, so organic production alternatives are sought, which have positive effects on crop yield and quality. Theobjective of the present research was to evaluate the use of different substrates in the growth, yield and quality of the Chichen Itzá hybrid habanero pepper in greenhouse, establishing four treatments with the following substrates and mixtures: T1: 100% earthworm humus with organic management (ORG-LOM); T2: earthworm humus mixture: regional soil: gravel in proportion 1:1:1 (v/v/v) with organic management (ORG-LSG); T3: earthworm humus mixture: river sand: gravel in proportion1:1:1 (v/v/v) with organic management (ORGRICOMPOSTA); and as a control T4: chemically managed river sand (QUIM-AR). The experiment was establishedunder a design of random complete blocks. The ORG-LOM treatment showed the best results, average plant height of 192.6 cm, stem diameter of 19.1 mm, number of flowers and fruits of 33.84 and 35.8% respectively of the total obtained, and yield per plant of 616.41 g, In addition, the fruit weight was 7.8 g, with length of 35.7 mm, diameter of 25.76 mm, pericarp thickness of 2.08 mm and number of lobules of 3.44. In all the variables evaluated, treatment with 100% earthworm humus substrate and organic management (ORG-LOM) was the best.
Keywords: Organic fertilizers; growth; oaxaca; yield; humid tropics